2013
DOI: 10.1002/adom.201300201
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Change Nanodot Material for an Optical Memory

Abstract: A sputtered phase-change material, Ge 10 Sb 90 , processed into dots with a height and diameter of 50 nm, shows rapid crystallization triggered by 300 ps laser excitation. Crystallization takes place with a short time delay of approximately 70 ns for a sample with Sb seed layers. The delay becomes just 15-20 ns when a NiCr layer is provided to control the heating-cooling profi le. The nanodot sample requires less energy for crystallization, with a large optical change equivalent to that of the blanket fi lm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…In the case of the isolated amorphous Ge 10 Sb 90 nanoparticles, there are no such interfaces at all, resulting in the considerable increase in crystallization time. The rather lengthy ¦t c 's of the Ge 10 Sb 90 nanoparticles compared with those determined by Yamada et al 10) are mainly due to the difference in sample structure, i.e., smaller thickness (10 nm) in the nanoparticles of our study (50 nm in the case of Yamada et al) or the absence of additional layers, such as the NiCr layer, which maintains the temperature of the nanoparticles at a high level, and the Sb seed layer, which assists crystallization. These reasons are all effective in realizing ¦t c 's of Ge 10 Sb 90 nanoparticles comparable to those of the blanket film.…”
Section: A (Amorphous)mentioning
confidence: 56%
See 1 more Smart Citation
“…In the case of the isolated amorphous Ge 10 Sb 90 nanoparticles, there are no such interfaces at all, resulting in the considerable increase in crystallization time. The rather lengthy ¦t c 's of the Ge 10 Sb 90 nanoparticles compared with those determined by Yamada et al 10) are mainly due to the difference in sample structure, i.e., smaller thickness (10 nm) in the nanoparticles of our study (50 nm in the case of Yamada et al) or the absence of additional layers, such as the NiCr layer, which maintains the temperature of the nanoparticles at a high level, and the Sb seed layer, which assists crystallization. These reasons are all effective in realizing ¦t c 's of Ge 10 Sb 90 nanoparticles comparable to those of the blanket film.…”
Section: A (Amorphous)mentioning
confidence: 56%
“…We thus performed several experiments to determine whether nanoparticles subjected to pulsed laser irradiation can be crystallized as rapidly as phase-change films. [8][9][10] In this study, we concentrated on two types of typical high-speed phase-change material: Ge 2 Bi 2 Te 5 11) and Ge 10 Sb 90 . 12) The nanoparticles of these materials were designed and fabricated on the basis of the calculations of their reflectivities.…”
mentioning
confidence: 99%
“…Phase change materials (PCMs) are a special group of chalcogenides with a peculiar combination of physical properties that have a variety of important applications in non-volatile electronic, optical and photonic data storage devices [18,19,20,21,22,23], memristors and processors [24,25,26,27,28], spintronics [29,30,31,32,33], display and data visualization applications [34], and so on. PCMs can undergo rapid and reversible phase transitions between an amorphous and a crystalline phase upon heating.…”
Section: Introductionmentioning
confidence: 99%
“…18,19) Regarding optical BPM, Yamada et al demonstrated that Ge 10 Sb 90 amorphous nanodots with a diameter of 50 nm show rapid crystallization (15-70 ns) upon 300 ps of laser irradiation and that the laser energy required for crystallization is smaller for nanodots than that for a film. 20) Also, an inserted layer with a low thermal conductivity, such as NiCr, suppresses heat diffusion and accelerates crystal growth. In previous studies, although the thermal design of nanodots was considered, the optimization of nanodots was still insufficient to enhance the near-field interactions with the antenna.…”
Section: Introductionmentioning
confidence: 99%